Use of pooled samples to assess human exposure to parabens, benzophenone-3 and triclosan in Queensland, Australia. (December 2015) - Heffernan, A.L.; Baduel, C.; Toms, L.M.L.; Calafat, A.M.; Ye, X.; Hobson, P.; Broomhall, S.; Mueller, J.F.
Abstract: Parabens, benzophenone-3 and triclosan are common ingredients used as preservatives, ultraviolet radiation filters and antimicrobial agents, respectively. Human exposure occurs through consumption of processed food and use of cosmetics and consumer products. The aim of this study was to provide a preliminary characterisation of exposure to selected personal care product chemicals in the general Australian population. De-identified urine specimens stratified by age and sex were obtained from a community-based pathology laboratory and pooled ( n  = 24 pools of 100). Concentrations of free and total (sum of free plus conjugated) species of methyl, ethyl, propyl and butyl paraben, benzophenone-3 and triclosan were quantified using isotope dilution tandem mass spectrometry; with geometric means 232, 33.5, 60.6, 4.32, 61.5 and 87.7 ng/mL, respectively. Age was inversely associated with paraben concentration, and females had concentrations approximately two times higher than males. Total paraben and benzophenone-3 concentrations are significantly higher than reported worldwide, and the average triclosan concentration was more than one order of magnitude higher than in many other populations. This study provides the first data on exposure of the general Australian population to a range of common personal care product chemical ingredients, which appears to be prevalent and warrants further investigation. Graphical abstract: Highlights: First characterisation of urinary parabens, TCS and BP-3 in an Australian population. 24 urine pools consisting of 100 individual specimens each, pooled by age and sex. Paraben concentrations significantly higher in children. Australian population concentrations significantly higher than many others globally.